The significance and challenges of turnover and retention of millennial professionals - Kathrine Anne Minzlaff; Stephen Palmer; Annette Fillery-Travis (Journal of Work-Applied Management)
Purpose – This paper aims to provide readers with a comprehensive overview of the current state of the millennial literature, highlighting the significance and challenges of millennial professionals, their reported high turnover and the various recommendations designed to engage and retain them. Design/methodology/approach – An integrated review approach was applied to synthesise contemporary peer-reviewed articles, supplemented by legacy and grey literature and relevant book chapters, to comprehensively explore and construct a cohesive overview of the current research on the millennial workforce. Findings – Within the wealth of available information, examining the various studies on millennial turnover reveals diverse theories, evidence and opportunities for advancement, underscoring the necessity for more robust empirical studies. The investigation identified three overarching retention strategy themes: (1) intergenerational conflict management, (2) workplace adaptations and (3) solutions rooted in a protean career orientation. In alignment with protean career concepts, coaching shows promise as an underexplored option. Practical implications – This article holds practical significance by offering researchers a comprehensive and cohesive overview of the millennial literature. Additionally, it gives organisations a novel perspective on the crucial role coaching can play in engaging and retaining millennial employees. Originality/value – The increased focus on retaining millennial workers in recent decades has spurred a proliferation of articles and books on this subject. However, this body of research remains fragmented, lacking an overview that provides a clear picture of its current state. This review aims to bridge this gap.